GAMBARAN SINDROMA DISPEPSIA FUNGSIONAL PADA MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS RIAU ANGKATAN 2014 - Rizky Nanda Putri; Yanti Ernalia; Eka Bebasari (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
ABSTRACTFunctional dyspepsia syndrome is collection of symptoms that consist discomfort in the upper abdomen (epigastric), heartburn, bloating, post prandial fullness and accompany with nausea, vomiting and bleching. Functional dyspepsia syndrome has multifactorial causes including consumptsion of high risk food such as spicy, acidic food and irritating drink. This research used a descriptive cross - sectional method to describe profile of functional dyspepsia syndrom in student of Faculty of Medicine University of Riau Generation 2014 with 138 respondent that included this research. This study used a questionaire to assess functional dyspepsia syndrome incidence and questionnaires FFQ to assess the frequency of risk food consumption habits. The results of this reasearch, 77 persons ( 55.8 % ) were functional dyspepsia syndrome. There were 74 persons (81,4%) with dyspepsia syndrom who frequently consume the spicy food, 72 persons (91,1%) who frequently consume the acidic food, and 39 persons (69,6%) who frequently consume the iritative drinking. The results of this research, respondent with dyspepsia syndrome more frequently eat spicy , acidic food and irritative drink that was compared with those who did not complain of dyspepsia syndrome.Keywords: syndrome dyspepsia, FFQ, food consumptsion and risk drinking habbit